2010
DOI: 10.1159/000277762
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis Insensitive to Systemic Terbinafine and Azole Treatments Reveals Non-Dermatophyte Moulds as Infectious Agents

Abstract: Background: Dermatophytes are the main cause of onychomycoses, but various non-dermatophyte filamentous fungi are often isolated from abnormal nails. Objective: Our aim was the in situ identification of the fungal infectious agent in 8 cases of onychomycoses which could not be cured after systemic terbinafine and itraconazole treat- ment. Methods: Fungal DNA was extracted from nail samples, and infectious fungi were identified by restriction fragment length polymorphism (RFLP) of amplified fungal ribosomal DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 33 publications
2
53
0
5
Order By: Relevance
“…The TRFLP assay does not allow the identification of dermatophytes to the species level, but in practice, identifying the genus to which an infecting fungus belongs is what is most relevant for the dermatologist with respect to onychomycosis. The two anthropophilic species T. rubrum and T. interdigitale are the causes of 99% of tinea unguium (22,31,35,37), and both species respond well to standard treatment with azoles and terbinafine, whereas special treatments may need to be prescribed for NDF onychomycosis (4). In other tinea infections, in particular tinea capitis, the treatment sometimes varies, depending on the species involved, and therefore, only in these cases would species determination be of any use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TRFLP assay does not allow the identification of dermatophytes to the species level, but in practice, identifying the genus to which an infecting fungus belongs is what is most relevant for the dermatologist with respect to onychomycosis. The two anthropophilic species T. rubrum and T. interdigitale are the causes of 99% of tinea unguium (22,31,35,37), and both species respond well to standard treatment with azoles and terbinafine, whereas special treatments may need to be prescribed for NDF onychomycosis (4). In other tinea infections, in particular tinea capitis, the treatment sometimes varies, depending on the species involved, and therefore, only in these cases would species determination be of any use.…”
Section: Discussionmentioning
confidence: 99%
“…Routinely, one portion of each clinical sample was examined in a dissolving solution using a fluorochrome (4,5,30). The solution was prepared by dissolving 1 g of sodium sulfide (Na 2 S) (Sigma, St. Louis, MO) in 7.5 ml distilled water and subsequently adding 2.5 ml ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the classical systemic treatments for onychomycosis caused by dermatophytes (e.g. itraconazole, fluconazole and griseofulvin) may fail when the nail infection is caused by NDMs 15 . There is also a recommendation for topical amphotericin B to be considered as a first-line treatment of NDM onychomycosis 6 .…”
mentioning
confidence: 99%
“…Efinaconazole possesses broader-spectrum antifungal activity than existing antifungals against dermatophyte and nondermatophyte molds and yeasts (14). It has potent in vitro antifungal activity against nondermatophytes, such as Scopulariopsis brevicaulis and Fusarium species, which cause nail infections that respond poorly to oral drugs (15). Thus, efinaconazole may be effective in treating nondermatophyte onychomycosis.…”
mentioning
confidence: 99%